Impact of pre-therapeutic fasting plasma glucose on survival outcomes in advanced non-small cell lung cancer patients - Liu, Feiwen; Luo, Min; Wang, Fang; Liang, Ting; Wang, Xiaochen (Frontiers in Endocrinology, 2026)
PurposeThe necessity of tight glycemic management in non-small cell lung cancer (NSCLC) remains controversial. This study aimed to determine whether baseline fasting plasma glucose (FPG) levels could serve as an independent prognostic marker for survival outcomes in advanced NSCLC.Patients and methodsThis study included 960 patients with advanced NSCLC, who were categorized into low (< 3.9 mmol/L), normal (3.9–6.1 mmol/L), and high FPG groups (> 6.1 mmol/L) based on pre-treatment FPG levels. The analyzed covariates included demographics, clinical characteristics, oncogenic mutation status, and first-line treatments. Survival curves with log-rank tests were estimated to compare survival differences between groups. Univariate and multivariate Cox proportional hazards regression were performed to investigate the prognostic factors. Furthermore, smooth curve fitting and piecewise Cox regression were used to explore the non-linear relationships between FPG and mortality risk, while subgroup analyses were employed to test interactions.ResultsBoth low (12.0 vs. 18.5 months, P = 0.0093) and high (14.4 vs. 18.5 months, P = 0.0049) FPG levels were significantly associated with shorter median survival times compared to normal FPG levels. Multivariable analyses further identified low FPG (HR 1.41, 95% CI 1.06–1.88; P = 0.0196) and high FPG (HR 1.43, 95% CI 1.11–1.85; P = 0.0059) as independent prognostic risk factors. Smooth curve fitting and piecewise Cox proportional hazards models revealed a negative linear relationship between FPG levels and mortality risk (HR 0.70, 95% CI 0.52–0.94; P = 0.0185) when FPG was below the breakpoint of 4.46 mmol/L, and a positive linear relationship (HR 1.11, 95% CI 1.04–1.19; P = 0.0015) when FPG exceeded the breakpoint. Subgroup analyses consistently supported these findings across all patient subgroups, with no specific population exhibiting distinct outcomes.ConclusionAbnormal FPG levels are independent risk factors for the long-term prognosis of advanced NSCLC. Further prospective multicenter studies are needed to confirm these associations and clarify whether glycemic assessment and management influence survival outcomes.